EVALUATION OF THE INITIAL DEVELOPMENT OF CONILON COFFEE CLONES (Coffea canephora) - CONTARATO, Cristiano Cezana; SOBREIRA, Fabrício Moreira; TOMAZ, Marcelo Antonio; JESUS JUNIOR, Waldir Cintra de; FONSECA, Aymbiré Francisco Almeida da; FERRÃO, Maria Amélia Gava; FERRÃO, Romário Gava (Scientia Agraria, 2010)
The ‘Vitória Incaper 8142’ variety of conilon coffee (Coffea canephora), presents superior productivity in relation to the others released so far. It consists of thirteen elite clones, whose cultivation is performed in lines. This work aimed to quantify the initial development of the clones which compose ‘Vitória Incaper 8142’ variety. The experiment was conducted in greenhouse, under a completely randomized design, with 13 treatments (clones) and seven repetitions. The plants were cultivated in vases and evaluated by 210 days after plantation. The 1V, 2V, 8V, 11V and 13V clones presented superior development in relation to the others concerning leaf number, plant height, plagiothropic branch emission, stem dry matter, root dry matter, air part dry matter and total dry matter. In general, this cultivar presents two groups of clones concerning the development by 210 days of plantation. The data indicates that the management can be different among the clones since the initial stage and that studies involving different environments are necessary in order to confirm these results.